A Structural and Mindset Bureaucratic Reform Agenda for Jokowi’s Second Term - Faedlulloh, Dodi; Yulianto, Yulianto; Karmilasari, Vina (UI Scholars Hub, 2021)
This article analyzes bureaucratic reforms for the second period of Jokowi’s leadership—the last stage of the grand design for bureaucratic reform. This moment is the last chance for Jokowi to shows his commitment to good governance. However, there are things that cannot be denied, the experience of the last five years (2014-2019) of Jokowi's leadership still leaves a lot of homework that needs to be addressed. The bureaucracy performance is still low. The research design in this article uses descriptive research methods supported by a literature study approach that traces the actual secondary data as a study material. The results of this study predict the two aspects mentioned by Jokowi in the